Global foot-and-mouth disease research update and gap analysis: 4 – Diagnostics - Knight-Jones, Theodore J.D.; Robinson, L.; Charleston, B.; Rodríguez, L.L.; Gay, C.G.; Sumption, Keith J.; Vosloo, W. (Hindawi Limited, 2016)
This study assessed knowledge gaps in foot-and-mouth disease (FMD) research in the field of diagnostics. The study took the form of a literature review (2011–15) combined with research updates collected in 2014 from 33 institutes from around the world. Findings were used to identify priority areas for future FMD research. Molecular and genetic technologies, including sequencing, are developing at an increasing rate both in terms of capability and affordability. These advances potentiate progress in many other fields of research, from vaccine development to epidemiology. The development of RT-LAMP represents an important breakthrough allowing greater use and access to molecular diagnostics. It is now possible to determine virus serotype using PCR, although only for certain virus pools, continued progress is needed to cover the global spectrum of FMD viruses. Progress has also been made in the development of pen-side rapid diagnostics, some with the ability to determine serotype. However, further advances in pen-side serotype or strain determination would benefit both FMD-free countries and endemic countries with limited access to well-resourced laboratories. Novel sampling methods that show promise include air sampling and baited ropes, the latter may aid sampling in wildlife and swine. Studies of infrared thermography for the early detection of FMD have not been encouraging, although investigations are ongoing. Multiplex tests have been developed that are able to simultaneously screen for multiple pathogens with similar clinical signs. Crucial for assessing FMDV freedom, tests exist to detect animals that have been infected with FMDV regardless of vaccination status; however, limitations exist, particularly when testing previously vaccinated animals. Novel vaccines are being developed with complementary DIVA tests for this purpose. Research is also needed to improve the current imprecise approaches to FMD vaccine matching. The development of simple, affordable tests increases access to FMD diagnostics, greatly benefiting regions with limited laboratory capacity.